2023
DOI: 10.1002/ffj.3729
|View full text |Cite
|
Sign up to set email alerts
|

A sensory characterization of some N‐heterocycles in model spirit matrix: Influence of ethanol and several chemical features on aroma perception

Abstract: The qualitative spirit ageing bouquet, developed during maturation in oak casks through a complex transformation process, can result in a broad palette of nuances where roasted and nutty aromas are often identified. Nitrogen heterocycles (pyrazines, thiazoles, pyrroles), produced during the heating step of the barrel‐manufacturing, contribute to the perception of these nuances. However, their specific sensory characteristics within the spirit matrix have been poorly studied until now. The current study consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 90 publications
1
4
0
Order By: Relevance
“…2‐Methyl‐3‐(methyldisulfanyl)furan imparted a roasted meat aroma, and furfuryl methyl disulfide had a roast odor. Among the four pyrazines studied, RDTs were continuously decreased with the increasing number of alkyl substituents attached to the ring, which was consistent with the result that both odor detection and recognition threshold values decreased in a spirit model medium (Goullet et al., 2023). Quantitative structure–activity relationship models of pyrazine‐based aroma compounds suggested a conformational and steric effect on the interaction with active sites of olfactory receptors (Buchbauer et al., 2000; Pal et al., 2013).…”
Section: Resultssupporting
confidence: 86%
“…2‐Methyl‐3‐(methyldisulfanyl)furan imparted a roasted meat aroma, and furfuryl methyl disulfide had a roast odor. Among the four pyrazines studied, RDTs were continuously decreased with the increasing number of alkyl substituents attached to the ring, which was consistent with the result that both odor detection and recognition threshold values decreased in a spirit model medium (Goullet et al., 2023). Quantitative structure–activity relationship models of pyrazine‐based aroma compounds suggested a conformational and steric effect on the interaction with active sites of olfactory receptors (Buchbauer et al., 2000; Pal et al., 2013).…”
Section: Resultssupporting
confidence: 86%
“…Heterocyclic compounds have vital importance in synthetic organic chemistry due to their roles in many naturally occurring molecules, as well as their crucial significance in the fields of pharmaceuticals and cosmetic industries 1,2 . These compounds mostly contain oxygen, sulphur and nitrogen atoms in their structures and are found in food flavours and fragrances, possessing valuable organoleptic characteristics 3,4 . Among these heterocycles, isoxazoline seems to be an attractive option since limited studies have been reported regarding their odour characteristics so far 5 .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These compounds mostly contain oxygen, sulphur and nitrogen atoms in their structures and are found in food flavours and fragrances, possessing valuable organoleptic characteristics. 3,4 Among these heterocycles, isoxazoline seems to be an attractive option since limited studies have been reported regarding their odour characteristics so far. 5 Therefore, the synthesis of new heterocycles having potential fragrant properties is highly desirable and challenging.Conventional 1,3-dipolar cycloaddition reactions are one of the best tools to provide heterocyclic molecules in a single synthetic step, and depending on the substituents of the starting materials, the regio-and/or stereochemistry of the products can be controlled.…”
mentioning
confidence: 99%
See 2 more Smart Citations